A theory of Justice. (Oxford Oxford University Press, 1973)
Rawls sets out the principles of justice that free and rational persons would accept in an initial position of equality.
Includes bibliographical references.
Keywords: Justice; Etica; Filosofia contemporanea; Filosofia politica; Rechtvaardigheid; Justice -- Philosophical aspects